Cutaneous Metastasis in the Setting of Both Colon and Breast Primary Malignancies - Mary Junak; Hunter Jecius; Jennifer Erdrich (Case Reports in Gastrointestinal Medicine)
Colorectal cancer (CRC) is the third most diagnosed cancer in the United States, and many patients unfortunately have metastases at the time of their diagnosis. Cutaneous metastases of CRC have been reported in few journals and primarily as case reports due to their rarity. Here, we present the case of an 83-year-old woman with recently resected colon cancer, T4aN1bMx stage IIIB. She presented to our clinic for evaluation of a right midback mass, and a punch biopsy revealed dermal involvement by invasive, poorly differentiated carcinoma with epidermoid features. The mass was excised, and we ordered a PET scan in search of the primary tumor, which at that time was suspected to be of skin cancer origin. Surprisingly, this revealed a second malignancy triple-negative invasive ductal carcinoma of the left breast. The back mass stained positive for CK20, which was compatible with a metastasis from a colonic primary. After initially declining adjuvant therapy, the patient completed one cycle of capecitabine and oxaliplatin, which she tolerated poorly. She continued to further decline, developed widespread cutaneous metastases, and went home on hospice. Cutaneous lesions are an exceedingly rare site of metastasis for colon adenocarcinoma, and their clinical presentation can vary widely. It is important for providers to investigate any new skin lesion in a patient with a recent or remote history of malignancy, even if there were no sites of distant metastasis at initial diagnosis.